Differential expression patterns of recombination-activating genes in individual mature B cells in juvenile idiopathic arthritis. Issue 10 (27th February 2006) - Faber, C; Morbach, H; Singh, S K; Girschick, H J
Abstract : Background: Re-expression of the recombination-activating genes ( RAG ) in peripheral B cells may be relevant in the development of autoreactive antibodies in autoimmune diseases. The presence of antinuclear antibodies (ANA) as a hallmark of oligoarticular juvenile idiopathic arthritis (o-JIA, early-onset type) indicates a breakdown in immunological tolerance. Aim: To examine the expression of RAG genes in peripheral blood mature B lymphocytes in patients with o-JIA. Methods: 777 memory B cells from peripheral blood, CD19+ CD27+ CD5+ or CD19+ CD27+ CD5−, isolated from three ANA+ children with o-JIA and three healthy age-matched children, were examined for the expression of RAG1 and RAG2 mRNA. mRNA transcripts of activation-induced cytidine deaminase and immunoglobulin G were searched to further determine their developmental stage. Results: mRNA was present for any of the two RAG genes in the B cells of children with JIA and controls. However, the predominance of RAG1 or RAG2 was different. A significantly decreased frequency of RAG2 -expressing memory B cells in both CD5+ and CD5− populations was noted in children with JIA (p<0.001), whereas the number of RAG1 -expressing B cells was slightly increased. The coordinate expression of both the RAG genes was a rare event, similar in the CD5+ populations (1% in controls, 2% in children with JIA), but different among the CD5− compartments (5% v 0%; p<0.01). Conclusion: These results argue for a reduced coordinate RAG expression in the peripheral CD5− memory B cells of patients with o-JIA. Thus, it was hypothesised that impaired receptor revision contributes to autoimmune pathogenesis in JIA.